STEAM education: review of literature - García Fuentes, Olalla; Raposo Rivas, Manuela; Martínez Figueira, Mª Esther (Revista Complutense de Educación, 2023)
The emergence of the maker movement and DIY philosophy (Do It Yourself) is causing the development of new methodologies, approaches and educational resources that are based on principles such as creation, collaboration and learning by doing. One of these new approaches is STEAM, which is based on the need to bet on science (S), technology (T), engineering (E), arts (A) and mathematics (M) in a cross-cutting and interdisciplinary way, in order to transform learning teaching processes into integrated and creative processes (Yakman, 2008a). METHOD. This work presents a review of literature on studies and research related to the STEAM educational approach, with the aim of obtaining an overview of the scientific literature produced on this between the years 2008-2019. 48 articles have been identified in Scopus, ERIC, Dialnet, GoogleScholar and Research Gate and analyzed 48 articles with a registration sheet prepared for this purpose. RESULTS. The results show that 83.3% of the investigations are of quantitative type, 12.5% qualitative and 4.1% mixed. Being objective the main (39.5%) the development, application and evaluation of proposals STEAM and the thematic recurrent (60.4%) the analysis of the combination of the art with the science, the technology or the mathematics. DISCUSSION. The investigation confirms that STEAM is positioned as an effective approach to increase the creativity, motivation and self-efficacy of students in learning teaching processes, provided that interdisciplinary and the real-life connection of the contents, through research or research methodologies, first. Being the main difficulties for the implementation of STEAM projects, the economic, curricular and temporal limitations of teachers.